Review on Lime-Treated Black Cotton Soil Strength Properties (International Journal of Engineering Management Science, 2025)
Black cotton soil, classified as expansive soil, is problematic for civil engineering construction due to its high shrink–swell potential, low bearing capacity, and high plasticity. Stabilization techniques are therefore adopted to improve its engineering behavior. Among the different stabilizers, lime has been extensively used due to its cost effectiveness, easy availability, and chemical compatibility with clay minerals. This paper presents a comprehensive review of the strength properties of lime-treated black cotton soil, focusing on changes in Atterberg limits, compaction characteristics, California Bearing Ratio (CBR), Unconfined Compressive Strength (UCS), and shear parameters. The review also highlights the mechanisms of soil–lime reactions, the effect of lime content, and curing periods on soil strength. Findings indicate that lime addition significantly enhances the strength and durability of expansive soils, making them suitable for use in subgrade and foundation applications.
Keywords: Atterberg limits; Black cotton (BC) soil; Compaction, Free Swelling Index (FSI); Lime; Coconut Shell Powder (CPS)